2013
DOI: 10.1108/jaoc-09-2010-0044
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal case study of target cost management implementation at a shipbuilding company

Abstract: Purpose – This paper aims to examine the implementation of target cost management (TCM) at a Japanese shipbuilding company. Design/methodology/approach – Using Rogers' Diffusion of Innovation as a framework, the paper presents a longitudinal in-depth case study of TCM implementation project to show the issues involved in implementing TCM. Findings – The paper finds that the diffusion of TCM is a consequence of a deliberate managerial activity – which in this case is the control over the TCM implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The issues covered in the articles published on TC were considerably diversified. For instance, Yasukata et al (2013) documented, using a case study, that the diffusion of TC was a result of deliberate managerial activity, while Kee and Matherly (2013) showed that the interdependence between product and production affect the usage of TC. Woods et al (2012), using a case study of MNC, documented how economic value added is introduced in TC system and provided preliminary evidence on how TC can, while using with other SMA techniques, play the bridging role in connecting strategic process and profit generation.…”
Section: Resultsmentioning
confidence: 99%
“…The issues covered in the articles published on TC were considerably diversified. For instance, Yasukata et al (2013) documented, using a case study, that the diffusion of TC was a result of deliberate managerial activity, while Kee and Matherly (2013) showed that the interdependence between product and production affect the usage of TC. Woods et al (2012), using a case study of MNC, documented how economic value added is introduced in TC system and provided preliminary evidence on how TC can, while using with other SMA techniques, play the bridging role in connecting strategic process and profit generation.…”
Section: Resultsmentioning
confidence: 99%
“…(Hesford, Lee, Van der Stede, & Young, 2007). On the other hand, few studies address issues related to structural cost management, notable exceptions include recent studies examining target costing (e.g., Dekker & Smidt, 2003;Kee & Matherly, 2006;Yasukata, Yoshida, Yamada, & Oura, 2013) and interorganizational cost management (e.g., Agndal & Nilsson, 2009;Fayard, Lee, Leitch, & Kettinger, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…A significant contribution to the development of theoretical aspects of cost accounting and calculating the prime cost of products (works, services) was made in works [1][2][3][4]. Various aspects of cost management automation are considered in the works [5][6][7][8].…”
Section: Literature Reviewmentioning
confidence: 99%